Мікробоценози ґрунтів з різним рівнем радіоактивного забруднення - Borzykh, A.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2001)
Microbial cenoses in soil with different levels of radioactive pollution have been investigated. Positive and negative significant correlation between quantity of microorganism from certain eco-trophical groups and levels of radioactive pollution have been found.